Hubungan Antara Pengetahuan, Sikap, Dan Motivasi Dengan Pemberantasan Sarang Nyamuk Di Desa Kudu Baki Sukoharjo - Puspitasari, Nisya Eka, Sri Darnoto S.KM M.PH, Anisa Catur Wijayanti, SKM., M.Epid (2015)
The chikungunya disease is endemic in village Kudu where there are 8 in sufferes 2013, in 2014 there were 12 sufferes. Prevention is the most inexpensive and effective can be done with 3M. It is important for the community to make the eradication of mosquitoes on a regular basis. Mosquito nest eradication is the eradication of mosquito larva in an effort to prevention of disease caused by mosquitoes. The purpose of this research was to determine the relationship between knowledge, attitude, and motivation of mosquito nest eradication in Kudu village. This research method using Analytic Observational design with Cross Sectional Study approach. The samples in this research is the head of family as much as 60 people. Using the Chi Square statistical tests using computer software. The result showed relationship between all knowledge with mosquito nest eradication value Continuity Corection of 8,629 and p-value of 0.003 < 0.05 (POR = 3,667; 95% CI: 1,587 - 8,472); the attittude of the mosquito nest eradication with the value of Continuity Correction 5,509 and p-value of 0,019 < 0,05 dan p-value 0,019 < 0,05 (POR = 2,949; 95% CI: 1,263 - 6,885); mosquito nest eradication with motivation value Continuity Correction of 11,397 and p-value of 0,001001 (POR 4,278; 95% CI: 1,870 - 9,78).